Dah maẖzan - Naṣrallāh H̱ān Ḥakīm (Navalkišor, 1915)
An account of the lives of Muḥammad and ʿAlī, and of the martyrdoms of Ḥasan and Ḥusain. - Beschreibung der Schlacht von Karbalā zwischen Ḥusain und Yazīd